2015
DOI: 10.1186/s12966-015-0192-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between active video gaming and other energy-balance related behaviours in adolescents: a 24-hour recall diary study

Abstract: BackgroundActive video games may contribute to reducing time spent in sedentary activities, increasing physical activity and preventing excessive weight gain in adolescents. Active video gaming can, however, only be beneficial for weight management when it replaces sedentary activities and not other physical activity, and when it is not associated with a higher energy intake. The current study therefore examines the association between active video gaming and other energy-balance-related behaviours (EBRBs).Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Widmar et al (2016) found SDB in respondents’ reporting of holiday eating behaviors [ 32 ]. Additionally, Simons et al (2015) found that non-active videogame playing young people underreported their sedentary gaming hours [ 51 ]. It is therefore unsurprising that differences were found between what respondents believed were important dog characteristics and what they believed others felt were important dog characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Widmar et al (2016) found SDB in respondents’ reporting of holiday eating behaviors [ 32 ]. Additionally, Simons et al (2015) found that non-active videogame playing young people underreported their sedentary gaming hours [ 51 ]. It is therefore unsurprising that differences were found between what respondents believed were important dog characteristics and what they believed others felt were important dog characteristics.…”
Section: Discussionmentioning
confidence: 99%
“… Hébert et al (2001) found that women with college educations working in the health system tended to underreport caloric intake. Simons et al (2015) found an underreporting of sedentary gaming hours among non-active videogame playing youths. Adams et al (2005) suggested that SDB led to an over reporting of physical activity among women in a self-reporting study.…”
Section: Introductionmentioning
confidence: 93%
“…The recall was based upon a recall diary used to measure AVG play in adolescents. 30 Relative RRV and Pmax of AVG versus SVG. The most liked type of AVG and SVG activities were provided as alternatives for the RRV testing session.…”
Section: Measurementsmentioning
confidence: 99%